Dosimetry - FitzGerald, Thomas J.; Bishop-Jodoin, Maryann (IntechOpen, 2022)
The book discusses multiple issues associated with modern dosimetry in physics and treatment planning and how investigators from diverse world centers and institutions approach problem-solving in these important areas. It examines topics including pretreatment validation and factors affecting reference dosimetry. It also addresses unique issues affecting pediatric populations as well as the modern role of thermoluminescence validation. Several chapters discuss intensity modulation, including defining modern problems associated with both treatment planning and the definition of tumor and normal tissue contours. Furthermore, the book examines the role of imaging as both a vehicle to define tumor targets and normal tissue as well as a tool for dose validation.